Inhaled and intranasal ciclesonide for the treatment of covid-19 in adult outpatients: CONTAIN phase II randomised controlled trial. (2nd November 2021) - Ezer, Nicole; Belga, Sara; Daneman, Nick; Chan, Adrienne; Smith, Benjamin M; Daniels, Shay-Anne; Moran, Kristen; Besson, Charlotte; Smyth, Louisa Y; Bartlett, Susan J; Benedetti, Andrea; Martin, James G; et al.
Abstract: Objective: To determine if inhaled and intranasal ciclesonide are superior to placebo at decreasing respiratory symptoms in adult outpatients with covid-19. Design: Randomised, double blind, placebo controlled trial. Setting: Three Canadian provinces (Quebec, Ontario, and British Columbia). Participants: 203 adults aged 18 years and older with polymerase chain reaction confirmed covid-19, presenting with fever, cough, or dyspnoea. Intervention: Participants were randomised to receive either inhaled ciclesonide (600 μg twice daily) and intranasal ciclesonide (200 μg daily) or metered dose inhaler and nasal saline placebos for 14 days. Main outcome measures: The primary outcome was symptom resolution at day 7. Analyses were conducted on the modified intention-to-treat population (participants who took at least one dose of study drug and completed one follow-up survey) and adjusted for stratified randomisation by sex. Results: The modified intention-to-treat population included 203 participants: 105 were randomly assigned to ciclesonide (excluding two dropouts and one loss to follow-up) and 98 to placebo (excluding three dropouts and six losses to follow-up). The median age was 35 years (interquartile range 27-47 years) and 54% were women. The proportion of participants with resolution of symptoms by day 7 did not differ significantly between the intervention group (42/105, 40%) and control group (34/98, 35%); absolute adjusted risk difference 5.5% (95% confidence interval −7.8% to 18.8%). Results might be limited to the population studied, which mainly included younger adults without comorbidities. The trial was stopped early, therefore could have been underpowered. Conclusion: Compared with placebo, the combination of inhaled and intranasal ciclesonide did not show a statistically significant increase in resolution of symptoms among healthier young adults with covid-19 presenting with prominent respiratory symptoms. As evidence is insufficient to determine the benefit of inhaled and intranasal corticosteroids in the treatment of covid-19, further research is needed. Trial registration: ClinicalTrials.gov NCT04435795 .